Enhanced activation of reward mediating prefrontal regions in response to food stimuli in Prader–Willi syndrome. Issue 6 (8th December 2006) - Miller, Jennifer L; James, G Andrew; Goldstone, Anthony P; Couch, Jessica A; He, Guojun; Driscoll, Daniel J; Liu, Yijun
Abstract : Background: Individuals with Prader–Willi syndrome (PWS) exhibit severe disturbances in appetite regulation, including delayed meal termination, early return of hunger after a meal, seeking and hoarding food and eating of non-food substances. Brain pathways involved in the control of appetite in humans are thought to include the hypothalamus, frontal cortex (including the orbitofrontal, ventromedial prefrontal, dorsolateral prefrontal and anterior cingulate areas), insula, and limbic and paralimbic areas. We hypothesised that the abnormal appetite in PWS results from aberrant reward processing of food stimuli in these neural pathways. Methods: We compared functional MRI blood oxygen level dependent (BOLD) responses while viewing pictures of food in eight adults with PWS and eight normal weight adults after ingestion of an oral glucose load. Results: Subjects with PWS demonstrated significantly greater BOLD activation in the ventromedial prefrontal cortex than controls when viewing food pictures. No significant differences were found in serum insulin, glucose or triglyceride levels between the groups at the time of the scan. Conclusions: Individuals with PWS had an increased BOLD response in the ventromedial prefrontal cortex compared with normal weight controls when viewing pictures of food after an oral glucose load. These findings suggest that an increased reward value for food may underlie the excessive hunger in PWS, and support the significance of the frontal cortex in modulating the response to food in humans. Our findings in the extreme appetite phenotype of PWS support the importance of the neural pathways that guide reward related behaviour in modulating the response to food in humans.